PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT.MULTI PRIMA MANDIRI - amos usaha fau (Fakultas Teknologi dan Ilmu Komputer, Universitas Prima Indonesia, 2021)
At the company PT. MULTI PRIMA MANDIRI always encounters obstacles in terms of the process of achieving performance. Every company needs to realize that to achieve good performance is influenced by a comfortable and clean work environment. So that employees have motivation and job satisfaction in the company PT. MULTI PRIMA MANDIRI. Based on the factors and my research entitled PT.MULTI PRIMA MANDIRI. to find out how much influence the work environment has on employee performance at PT. MULTI PRIMA MANDIRI. Then the method used is the Likert scale and SPSS. Based on the results of the t test, a significant value of 5% is obtained, then H1 is accepted or H0 is rejected. It can be seen that the influence of the work environment on employee performance at PT. MULTI PRIMA MANDIRI.